Interchangeability between Pneumococcal Conjugate Vaccines: A Systematic Review and Meta-Analysis - Ciapponi, Agustín (2016)
Objectives: To assess the efficacy, cost-effectiveness, immunogenicity, and safety related to the interchangeability between pneumococcal conjugate vaccines (PCVs) and vaccination schedules in pediatric population. Methods: Systematic searches were conducted in December 2010 and April 2015 for economic evaluations in MEDLINE, EMBASE, LILACS, and Cochrane Central Register of Controlled Trials. Web sites and databases from medical societies, experts, and associations related to the topic, proceedings or congressional annals, and doctoral theses were also searched. No language or temporal restriction was applied. We included randomized controlled trials, economic evaluations, and systematic reviews evaluating antibody response, cost-effectiveness, and effectiveness of PCVs' interchangeability. A Strengthening the Reporting of Observational Studies in Epidemiology-based checklist was used to assess the risk of bias in observational studies and a Cochrane approach for experimental/quasi-experimental studies. Pairs of reviewers independently selected (through the Web-based Early Reviewer Organizer Software), assessed the quality, and extracted the data of the studies. Discrepancies were resolved by consensus. We planned to perform meta-analysis whenever appropriate. Results: Forty-six of 202 studies were included. There was no direct information available on the interchangeability between PCVs. The immunogenicity and safety between the 10-valent PCV (PCV10) and the 7-valent PCV were similar when both vaccines were coadministered with other routine pediatric vaccines. PCV10 and 13-valent PCV (PCV13) were consistently more cost-effective than 7-valent PCV. Conclusions: There was no direct comparative information available on the interchangeability among PCVs, but they have pretty similar immunogenicity and safety. PCV10 versus PCV13 cost-effectiveness varied according to price, indirect effects, and indirect costs. PCV10 gains more quality-adjusted life-years because of the prevention of more frequent yet less severe events such as otitis media, and PCV13 prevents less frequent but more costly events such as invasive diseases.